Fluid Shifts and Heart Rate Responses During Prolonged Swimming - Nielsen, B. (Biomechanics and Medicine in Swimming, 1983)
During exercise, heart rate and cardiac output increase within the first few minutes after the start in proportion to the exercise intensity. The distribution of blood flow is changed through dilation in the working muscles and a vasoconstriction in the inactive regions. Later a vasodilation in the skin occurs, probably as a result of the increasing coretemperature. With prolonged exercise of moderate intensity, such as bicycling or running, a further gradual increase in heart rate takes place as the work continues. This rise may amount to 20-30 beats per min (bpm) during 2 hr of strenuous work. The "secondary" increase in heart rate could have various causes; for example, it has been attributed to the dehydration from sweating which leads to decreased blood volume and stroke volume. It could also be an effect of the vasodilation and increase in skin blood flow which produce a decrease in central blood volume and stroke volume; or, the contractility of the heart may have decreased as a sign of fatigue. In all these situations, compensatory reflexes would lead to an increased heart rate. During swimming, the heart rate is lower than that for exercise at the same metabolic rate in air. The reason may be that the horizontal position and hydrostatic pressure favor the filling of the heart, and that heat dissipation causes no problem in cool water due to the high heat conductivity and heat capacity of water. The effect of prolonged swimming on the secondary rise in heart rate was investigated. Both the breast stroke (predominantly arm work) and the isolated leg-kick of freestyle swimming were investigated and compared to bicycle exercise at the same metabolic rate.